Highly efficient organic light emitting diodes based on a D–A–D type dibenzothiophene derivative exhibiting thermally activated delayed fluorescence with small ΔEST. Issue 43 (14th October 2016) - He, Xin; Shan, Tong; Tang, Xiangyang; Gao, Yu; Li, Jinyu; Yang, Bing; Lu, Ping
Abstract : DPAC–DBTDO possesses a very small Δ E ST of 0.10 eV between S1 and T1 . A high external quantum efficiency of 13.1% is achieved in multi-layered OLEDs. Abstract : A new D–A–D type TADF material, namely DPAC–DBTDO, is constructed using 9, 9-diphenyl-9, 10-dihydroacridine as an electron donor and dibenzo[ b, d ]thiophene-5, 5-dioxide as an electron acceptor. DPAC–DBTDO possesses a very small Δ E ST of 0.10 eV between S1 and T1, which is the lowest value among DBTDO-derivatives. DPAC–DBTDO exhibits nearly 100% solid-state efficiency. A high external quantum efficiency of 13.1% is also achieved in multi-layered OLEDs.